SEBUAH MODEL BERBASIS PENGETAHUAN UNTUK PENGENDALIAN FORMASI SISTEM ROBOT MAJEMUK - Andi Adriansyah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
Study of multi-robot system has been popular in recent years. This system is able to reduce processing time of some processes, the cost and complexity of the system. However, multi-robot system also has some problems. One of the problems faced by these systems is how to control robots in a certain formation when carrying out its functions. Several methods have been offered to resolve the existing problems. This study tries to offer a method to solve the problem, by modeling the multi-robot systems and implement a control system in order to maintain a specific formation. The study attempted to use a controller based on knowledge base system. Model is developed using MATLAB software and simulated to determine the performance. Several experiments are conducted to determine the movement of the robot and its ability to maintain a specific formation. From the experiments it can be said that the modeling of multiple-robot system has been reliable. In addition, formation control actions have also been running well, although there should be further development.